Evaluation of circulating small extracellular vesicles derived miRNAs as biomarkers of early colon cancer: a comparison with plasma total miRNAs. Issue 1 (1st December 2019) - Min, Li; Zhu, Shengtao; Chen, Lei; Liu, Xiang; Wei, Rui; Zhao, Libo; Yang, Yuqing; Zhang, Zheng; Kong, Guanyi; Li, Peng; Zhang, Shutian
ABSTRACT: Early diagnosis of colon cancer (CC) is clinically important, as it can significantly improve patients' survival rate and quality of life. Although the potential role for small extracellular vesicles (sEVs) in early detection of many diseases has been repeatedly mentioned, systematic screening of plasma sEVs derived early CC specific biomarkers has not yet been reported. In this work, plasma sEVs enriched fractions were derived from 15 early-stage (TisN0M0) CC patients and 10 normal controls (NC). RNA sequencing identified a total number of 95 sEVs enriched fraction derived miRNAs with differential expression between CC and NC, most of which (60/95) was in well accordance with tissue results in the Cancer Genome Atlas (TCGA) dataset. Among those miRNAs, we selected let-7b-3p, miR-139-3p, miR-145-3p, and miR-150-3p for further validation in an independent cohort consisting of 134 participants (58 CC and 76 NC). In the validation cohort, the AUC of 4 individual miRNAs ranged from 0.680 to 0.792. A logistic model combining two miRNAs (i.e. let-7b-3p and miR-145-3p) achieved an AUC of 0.901. Adding the 3rd miRNA into this model can further increase the AUC to 0.927. Side by side comparison revealed that sEVs miRNA profile outperformed cell-free plasma miRNA in the diagnosis of early CC. In conclusion, we suggested that circulating sEVs enriched fractions have a distinct miRNA profile in CC patients, and sEVs derived miRNA could be used as a promising biomarker to detect CC at an early stage.